2013
DOI: 10.1021/jp408061k
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Myoglobin Unfolding in the Presence of Guanidinium Hydrochloride and Ionic Liquids in Solution

Abstract: The use of ionic liquids in biochemical and biophysical applications has increased dramatically in recent years due to their interesting properties. We report results of a thermodynamic characterization of the chaotrope-induced denaturation of equine myoglobin in two different ionic liquid aqueous environments using a combined absorption/fluorescence spectroscopic approach. Denaturation by guanidinium hydrochloride was monitored by loss of heme absorptivity and limited unfolding structural information was obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 48 publications
7
36
0
Order By: Relevance
“…We compare results for four different ILs: 1-butyl-3-methyl imidazolium tetrafluoroborate (BMIBF 4 ); 1-butyl-3-methyl pyrrolidinium tetrafluoroborate (PyrrBF 4 ); 1-ethyl-3methyl imidazolium acetate (EMIAc); and tetramethylguanidinium acetate (TMGAc). In a previous report [7], we quantified myoglobin thermodynamic stabilities in aqueous solutions of BMIBF 4 and EMIAc and showed that BMIBF 4 destabilizes myoglobin while EMIAc has minimal effect on the protein stability.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…We compare results for four different ILs: 1-butyl-3-methyl imidazolium tetrafluoroborate (BMIBF 4 ); 1-butyl-3-methyl pyrrolidinium tetrafluoroborate (PyrrBF 4 ); 1-ethyl-3methyl imidazolium acetate (EMIAc); and tetramethylguanidinium acetate (TMGAc). In a previous report [7], we quantified myoglobin thermodynamic stabilities in aqueous solutions of BMIBF 4 and EMIAc and showed that BMIBF 4 destabilizes myoglobin while EMIAc has minimal effect on the protein stability.…”
Section: Introductionmentioning
confidence: 97%
“…The structures and stabilities of proteins in aqueous ionic liquid (IL) solutions have been the focus of numerous recent reports in the literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Such studies are motivated by the utilization of ILs in several different biomedical and biochemical techniques [5,[16][17][18][19][20][21], where ILs are present as solutes in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations